Streptococcus pneumoniae-associated pneumonia complicated by purulent pericarditis: case series - Catia Cillóniz; Ernesto Rangel; Cornelius Barlascini; Ines Maria Grazia Piroddi; Antoni Torres; Antonello Nicolini (Jornal Brasileiro de Pneumologia, 2015)
AbstractObjective: In the antibiotic era, purulent pericarditis is a rare entity. However, there are still reports of cases of the disease, which is associated with high mortality, and most such cases are attributed to delayed diagnosis. Approximately 40-50% of all cases of purulent pericarditis are caused by Gram-positive bacteria, Streptococcus pneumoniae in particular.Methods: We report four cases of pneumococcal pneumonia complicated by pericarditis, with different clinical features and levels of severity.Results: In three of the four cases, the main complication was cardiac tamponade. Microbiological screening (urinary antigen testing and pleural fluid culture) confirmed the diagnosis of severe pneumococcal pneumonia complicated by purulent pericarditis.Conclusions: In cases of pneumococcal pneumonia complicated by pericarditis, early diagnosis is of paramount importance to avoid severe hemodynamic compromise. The complications of acute pericarditis appear early in the clinical course of the infection. The most serious complications are cardiac tamponade and its consequences. Antibiotic therapy combined with pericardiocentesis drastically reduces the mortality associated with purulent pericarditis.